Synthesis and SAR studies of 3-phenoxypropyl piperidine analogues as ORL1 (NOP) receptor agonists - Palin, Ronald; Barn, David R.; Clark, John K.; Cottney, Jean E.; Cowley, Phillip M.; Crockatt, Marc; Evans, Louise; Feilden, Helen; Goodwin, Richard R.; Griekspoor, Frank; Grove, Simon J.A.; Houghton, Andrea K.; et al. (Bioorganic & medicinal chemistry letters, 2005)
A series of potent and soluble ORL1 agonists was prepared and evaluated. Compound 41 showed antinociceptive properties in mouse formalin paw test (ED 50 = 1.07 μmol/kg). A series of 3-phenoxypropyl piperidine analogues have been discovered as novel ORL1 receptor agonists. Structure–activity relationships have been explored around the 3-phenoxypropyl region with several potent and selective analogues identified.